D'Sava: edible instant food seasoning wrap made from biodegradable plastic waste cassava peel with aloe vera addition as antioxidant / Eriko Elsa Daje ... [et al.] - Elsa Daje, Eriko; Navita Tsanie, Ola; Nur Insani, Mutiara; Yuliana, Astrid; Pramudita, Ika; Alinda H, Refina (2022)
Plastic waste is one of the biggest issues that has been going on for a long time and still has not been resolved up until now. The dependence of the world community on plastic waste makes the production of plastic waste continue to increase every year. Indonesia is the second largest contributor to plastic waste in the oceans in the world after China. The Indonesian Plastic Industry Association (INAPLAS) and the Central Statistics Agency (BPS) recorded that Indonesia's plastic waste product that was thrown into the ocean reached 3.2 million tons out of a total of 64 million tons of plastic waste per year. The purpose of this research is to make plastic that is edible and can also preserve food as an instant food seasoning wrap. Cassava peel waste can be used as packaging for biodegradable instant food seasonings that are zero-emission and are named D'Sava or biodegradable cassava. D'Sava can be eaten because it is rich in nutrients and contains high antioxidants from a mixture of aloe vera so that it can preserve food. D'Sava can replace the use of synthetic plastic which is very dangerous. A total of 1 baking pan with a size of 30 cm2 can produce 28 units of packaging with a size of 4 cm2. D'Sava will last longer as food packaging. Because of its ability to not getting exposed to direct air, it will be a good replacement for packaging that is made of synthetic plastic.